The The Influence of Parental Involvement and Work on Early Childhood Language Development - Tedy Andrian; Ira Makalim; Supriyadi Supriyadi (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2025)
This study aims to analyze the influence of parental involvement and work on early childhood language development. The research method used is quantitative with a survey approach. The research sample consisted of 45 parents of children aged 5-6 years who attended PAUD MELATI 01 Warakas, Tanjung Priok, North Jakarta. Instruments include a parent engagement questionnaire with Cronbach's Alpha reliability of 0.941, a parent work questionnaire (α = 0.81), and a child language development instrument based on the National Standards for Early Childhood Education. The results of the double linear regression analysis showed that parental involvement had a significant effect on children's language development (p < 0.05), while parental work did not have a significant effect. Simultaneously, the combination of parental involvement and work explained 50.1% of the variability of children's language development. These results emphasize the importance of active parental involvement in supporting early childhood language skills.